'Dead' ransomware actors re-emerge. Issue 8 (August 2021) - Unknown
Abstract : Just a couple of weeks after the apparent disappearance of the Darkside, REvil and Avaddon ransomware groups, two new threat actors have emerged. And there's a strong possibility that they are the same people with new branding.